2010
DOI: 10.1186/1824-7288-36-18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weaning biscuits on the nutritional profile and the cognitive development in preschool children

Abstract: AimTo study the effect of weaning biscuits supplementation of the nutritional parameters and cognitive performance of the selected children.MethodsThree primary schools situated in Salem District, Tamilnadu, India were selected. A total number of 150 school children, 61 from primary school I, 46 from primary school II and 43 from primary school III comprised the study sample. About 80 primary school children with Grade II malnutrition were selected for the experimental study. Home diet without any supplementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The interesting finding in the present study was that after 3 months of providing cowpea supplemented biscuits to the children from experimental group, they improved significantly on all the domains of cognitive development in comparison to those for control II and control I group. The findings of the present study are in line with that of Nazni et al, who reported that after three months supplementation of potato flour biscuits, cognitive performance was good in the supplemented group children as compared to the control group [20]. Similarly, supplementation of multiple-micronutrient-fortified fruit powder beverage for 16 weeks showed significant improvements in cognitive performance [21].…”
Section: Mean Score In Various Domains Of Cognitive Developmentsupporting
confidence: 92%
“…The interesting finding in the present study was that after 3 months of providing cowpea supplemented biscuits to the children from experimental group, they improved significantly on all the domains of cognitive development in comparison to those for control II and control I group. The findings of the present study are in line with that of Nazni et al, who reported that after three months supplementation of potato flour biscuits, cognitive performance was good in the supplemented group children as compared to the control group [20]. Similarly, supplementation of multiple-micronutrient-fortified fruit powder beverage for 16 weeks showed significant improvements in cognitive performance [21].…”
Section: Mean Score In Various Domains Of Cognitive Developmentsupporting
confidence: 92%
“…In contrast, increased serotonin is associated with a sense of well-being and elevates mood. Wheat biscuits added to the diets of malnourished Indian primary school-aged children actually improved cognitive ability (37).…”
Section: Davis' Point -Wheat Ingestion Alters Mood and Causes Mental mentioning
confidence: 97%
“…Studies conducted by Pradhan et al (2010) on male and female diabetic patients spread across different rural and urban locations, also showed that the glucose level was maintained after consuming multigrain chapati of finger millet and wheat in a ratio of 30:70. Another study by Nazni et al (2010) showed the positive impact of weaning biscuits supplements on the nutritional aspects and cognitive functions of children. Finger millet is gluten free and hence can be a boon for patients suffering from celiac disease (Pagano, 2006) as a strict gluten-free diet is currently the only treatment for this disease.…”
Section: Finger Millet: An Economically Important Nutraceutical Cropmentioning
confidence: 99%